2016
DOI: 10.1093/jrr/rrw051
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the distribution and function of leukocytes after whole-body iron ion irradiation

Abstract: High-energy particle radiation could have a considerable impact on health during space missions. This study evaluated C57BL/6 mice on Day 40 after total-body 56Fe26+ irradiation at 0, 1, 2 and 3 gray (Gy). Radiation consistently increased thymus mass (one-way ANOVA: P < 0.005); spleen, liver and lung masses were similar among all groups. In the blood, there was no radiation effect on the white blood cell (WBC) count or major leukocyte types. However, the red blood cell count, hemoglobin, hematocrit and the CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…These investigations have shown that simulated cosmic radiation decreases the lymphocyte population ( 52 ), with a higher impact on B cells, followed by T cells (CD8+ > CD4+) and natural killer cells ( 53 55 ). The response and function of leukocytes are also altered by simulated cosmic radiation ( 55 ), and the effects are long lasting and dependent on the dose, the type of source, and the body compartment ( 56 – 59 ). Overall, these results are supported by investigations from other groups ( 60 , 61 ).…”
Section: Space Radiationmentioning
confidence: 99%
“…These investigations have shown that simulated cosmic radiation decreases the lymphocyte population ( 52 ), with a higher impact on B cells, followed by T cells (CD8+ > CD4+) and natural killer cells ( 53 55 ). The response and function of leukocytes are also altered by simulated cosmic radiation ( 55 ), and the effects are long lasting and dependent on the dose, the type of source, and the body compartment ( 56 – 59 ). Overall, these results are supported by investigations from other groups ( 60 , 61 ).…”
Section: Space Radiationmentioning
confidence: 99%
“…Sublethal doses delivered with carbon ion beams inhibited in vitro angiogenesis 67 and the expression of angiogenesis mediators 68 , 69 . In immune-competent mouse models, lung metastasis was significantly suppressed by carbon ion irradiation 66 , 70 .…”
Section: Introductionmentioning
confidence: 97%
“…2-Other studies indicated a clear decrease in CD8 count, and thus a clear increase in CD4:CD8 rate. [13] Where CD4 is more resistant to radiation at 2-Gray dose than CD8, but CD8's return to normal levels is faster than CD4's [14]. This theory proved to be striking, and after a time of exposure to nuclear bomb radiation, there was a clear variability in the cell count, with a normal CD4 cell count and a decrease in CD8 cell count in the exposed organisms [15] Plus, with the exception of only one report, the CD4 cell count increased in people exposed to radiation in the Chernobyl tragedy [15].…”
Section: Discussionmentioning
confidence: 99%